STUDY OF VARIABILITY, CORRELATION AND PATH ANALYSIS IN FORAGE SORGHUM [SORGHUM BICOLOR SORGHUM BICOLOR SORGHUM BICOLOR (L.) MOENCH] (L.) MOENCH] - RANA, H. R; KHER, H. R (The Bioscan, 2015)
Genetic variability, correlation and path analysis was studied for yield and its attributing characters in forty diverse genotypes of in forage sorghum [Sorghum bicolor (L.) Moench.A wide range of phenotypic variability was recorded for green fodder yield per plant and its component traits. In the present study magnitude of genetic coefficient of variation (GCV), phenotypic coefficient of variation (PCV), heritability and genetic advance as percentage of mean were recorded high for various characters like leaf: stem ratio, number of leaves per plant, green fodder yield per plant, stem girth and dry matter yield per plant. The results of Correlation analysis suggested that the magnitude of genotypic correlation were higher as compared to their corresponding phenotypic correlations indicating the inherent relationship among the characters studied. Green forage yield per plant was highly significant and positively correlated with stem girth, leaf length, leaf width and dry matter yield per plant at both genotypic and phenotypic level. These characters may be considered as important yield component in sorghum. Path coefficient analysis revealed high positive direct effect of dry matter yield per plant, stem girth and days to fifty per cent flowering. These traits had high magnitude of genotypic correlation with green forage yield per plant.